Techniques in Image Steganography using Famous Number Sequences (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In In the last decades, Steganography techniques have been applied in a variety of data files. The need of copyrightprotection in Music, in Photography e.t.c pushed the software companies to develop many steganographic systemswhich they use, in various areas, e.g., in digital assets (DRM). In this paper, we propose a number of methods forimage steganography using Catalan numbers and Lucas numbers and we show that they produce better resultsthan the technique using Fibonacci numbers. We are able to use Catalan and Lucas numbers since we haveproved that these sets of numbers satisfy similar conditions to those of the Theorem of Zeckendorf.